Imagination Matters When You Shop Online: The Moderating Role of Mental Simulation Between Materialism and Online Impulsive Buying - Li, Jing; Yang, Ruirui; Cui, JunJie; Guo, Yongyu (Psychology research and behavior management, 2019)
Several studies have demonstrated that materialistic people tend to engage in impulsive buying. However, how to help them reduce such irrational behavior, especially in online shopping context, is not known. This study aimed to explore whether mental simulation moderates the relationship between materialism and online impulsive buying. A total of 200 Chinese college students participated in the experiment. We adopted an imaginary priming paradigm to manipulate three types of mental simulation: process simulation (i.e., imagining the detailed process of purchasing goods), upward outcome simulation (i.e., imagining possible positive outcomes after purchasing), and downward outcome simulation (i.e., imagining possible negative outcomes after purchasing). Then we asked participants to make purchase decisions in a simulated online store. Results showed that mental simulation exerted a significant moderating effect. In the upward outcome simulation group, a higher level of materialism predicted more online impulsive buying. However, this association was not significant in the downward outcome simulation and process simulation groups. Our findings have implications for interventions in that mental simulation (process simulation or downward outcome simulation) can act as an effective way to help materialists reduce online impulsive buying.